Portal Venous Circulating Tumor Cells Undergoing Epithelial-Mesenchymal Transition Exhibit Distinct Clinical Significance in Pancreatic Ductal Adenocarcinoma - Pan, Yujin; Li, Deyu; Yang, Jiuhui; Wang, Ning; Xiao, Erwei; Tao, Lianyuan; Ding, Xiangming; Sun, Peichun; Li, Dongxiao (Frontiers in Oncology, 2021)
Background Much importance is attached to the clinical application value of circulating tumor cells (CTCs), meanwhile tumor-proximal CTCs detection has interested researchers for its unique advantage. This research mainly discusses the correlation of portal venous (PoV) CTCs counts in different epithelial-mesenchymal transition status with clinicopathologic parameters and postoperative prognosis in resectable pancreatic ductal adenocarcinoma patients (PDAC). Methods PDAC patients (n=60) who received radical resection were enrolled in this research. PoV samples from all patients and peripheral venous (PV) samples from 32 patients among them were collected to verify spatial heterogeneity of CTCs distribution, and explore their correlation with clinicopathologic parameters and clinical prognosis. Results CTCs detectable rate and each phenotype count of PoV were higher than those of PV. Patients with recurrence had higher PV and PoV epithelial CTCs (E-CTCs) counts than recurrence-free patients (P<0.05). Some unfavourable clinicopathologic parameters were closely related to higher PoV CTCs counts. Multivariate regression analysis demonstrated that PoV mesenchymal CTC (M-CTC)s≥1/5 ml was an independent risk factor for metastasis free survival (MFS) (P=0.003) and overall survival (OS) (P=0.043). Conclusions Our research demonstrated that portal venous was a preferable vessel for CTC test, and patients with PoV M-CTC≥1/5 ml had shorter MFS and OS time in resectable PDAC patients. PoV CTC phenotype detection has the potential to be a reliable and accurate tool to identify resectable PDAC patients with high tendency of postoperative metastasis for better stratified management.